SNARE–YELLOWKNIFE RELATIONS, DISTRICT OF MACKENZIE, N.W.T., CANADA - Ross, John V.; McGlynn, John C. (Canadian Journal of Earth Sciences, 1965)
Within the District of Mackenzie, N.W.T., Canada, Snare Group rocks unconformably overlie Yellowknife Group; both groups of rocks are Precambrian in age. Snare deformation has modified the already deformed Yellowknife rocks and examples are given of Yellowknife "basement" response to the varying styles of Snare "cover" deformation.